Association between pre-hospital care time and hospital mortality in victims of traffic accidents: Asociación entre tiempo de atención pre hospitalaria y la mortalidad hospitalaria en víctimas de accidentes de tránsito - Fernandez-Sandoval, María Jesús G. (2019)
Introduction: Traffic accidents (AT) are the first priority in health research in Peru, According to the World Health Organization (WHO) it is estimated that the economic costs of vehicle impact and injuries due to AT are 1 % and 1.5% of the Gross National Product (GNP) in low and middle income countries; In Peru it is approximately 1.5 - 2% of the Gross Domestic Product (GDP). Objective: To determine if there is an association between the time of prehospital care and hospital mortality in victims of traffic accidents. Methods: A systematic review was carried out through the literature search of related articles in indexing sources such as PubMed and BIREME. Results: Delays in the transfer of patients to the hospital and the lack of pre-hospital Emergency Medical System (SME) were significantly associated with an increase in mortality (P: 0.000) and the need for an SME as a prehospital care provider was significant predictor of emergency mortality with an adjusted odds ratio [OR] 2.19; 95% CI [1.88–2.55], and in the first 24 hours of admission with an adjusted OR 2.31; 95% CI [1.95–2.73]. Conclusion: The time of pre-hospital care in traffic accidents is significantly associated with hospital mortality, therefore, it is proposed to study factors associated with the longtime of pre-hospital care.